2015
DOI: 10.1097/dss.0000000000000355
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Response of 70% Trichloroacetic Acid CROSS in Atrophic Acne Scars

Abstract: The study showed that 70% of TCA is a safe and effective treatment option in all types of atrophic acne scars, especially in severe boxcar scars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 25 publications
0
28
0
7
Order By: Relevance
“…The clinical response was graded into: complete response (if there was complete resolution of lesions), partial response (if there was a reduction in the size and/or the total number of warts), and no response (if there was not any change in the size and/or the number of warts) (Moubasher, Hassan, Youssef, & Sabek, ). Side effects during the course of treatment were also recorded. (The verbal rating scale, with prescribed terms such as none, mild, moderate, severe, and unimaginable pain was used to access pain). Patients were asked to grade their satisfaction with the therapy by using a quartile grading system (0 unsatisfied, 1 slightly satisfied, 2 satisfied, or 3 very satisfied) (Agarwal & Gupta, ).…”
Section: Methodsmentioning
confidence: 99%
“…The clinical response was graded into: complete response (if there was complete resolution of lesions), partial response (if there was a reduction in the size and/or the total number of warts), and no response (if there was not any change in the size and/or the number of warts) (Moubasher, Hassan, Youssef, & Sabek, ). Side effects during the course of treatment were also recorded. (The verbal rating scale, with prescribed terms such as none, mild, moderate, severe, and unimaginable pain was used to access pain). Patients were asked to grade their satisfaction with the therapy by using a quartile grading system (0 unsatisfied, 1 slightly satisfied, 2 satisfied, or 3 very satisfied) (Agarwal & Gupta, ).…”
Section: Methodsmentioning
confidence: 99%
“…9,22 Of note, some studies included a total of 5 patients who were on isotretinoin for 3 or 6 months prior to CROSS method. 9,15 Both studies reported good results without resulting in keloid or hypertrophic scarring. One of these patients experienced prolonged, adherent crusting which persisted for about two weeks.…”
Section: Precare Instructionsmentioning
confidence: 99%
“…The patients were predominantly female except in three studies. [13][14][15] Patients ranged from age 9 to 52. The majority of the studies looked at patients with Fitzpatrick skin phototypes (FST) III-V. Four studies included FST II, 14,[16][17][18] and one study included FST I.…”
Section: Demographics and Clinical Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately a third patients with darker skin type may develop PIH, which may persist in some patients. [ 17 18 ] Better results are observed with 100% compared to 65% TCA CROSS. [ 19 ] Phenol (88%) has been used in place of TCA (90%) with comparable results in V and VI skin type.…”
Section: Hemical R Econstruction Of mentioning
confidence: 99%